Understanding Public Value Through Its Methods - Ćwiklicki, Marek; Pilch, Kamila (Journal of Public Governance, 2021)
Objectives: The article has two main purposes. On the one hand, it shows how public value is defined and through what management tools it is created. On the other hand, it presents how representatives of various scientific disciplines describe the desired features of instruments creating public value and, based on this, how they evaluate the existing tools.Research Design & Methods: We apply multiple factor analysis (MFA) on data collected from scholars from different scientific disciplines. The dimensions of various groups of methods described by the respondents made it possible to reveal the similarities and differences in their perceptions.Findings: The study demonstrates that a scientific disciplinal background can influence perceptions of the benefits of management methods to deliver public value. Knowledge of background can make public managers aware of prejudices towards particular tools as well as it helps identify the most adequate one for each dimension of public value.Contribution / Value Added: Our paper contributes to the body of knowledge of public value by showing how different perspectives can be integrated and helpful for describing diversified sets of tools. We outline how the respondents perceive the delivery of public value through management methods and, from this perspective, how they evaluate various tools.Article classification: research articleJEL classification: H11, H83, C38